Development of Research Competence of the Future Teacher in the Structure of Educational Process - Franchuk, Tetiana; Boiko, Igor (Pedagogical Discourse, 2025)
The article concerns the problem of the theory and practice of forming the future teacher’ research competence of in the process of his professional development. The goal is to form an approach to interpreting the essence of the research competence of a future specialist. It is based on the generalizing his functional capabilities, as well as identifying problems and potential development opportunities in the structure of the organization of the educational process. The position is substantiated that one of the basic reasons for the insufficient level of formation of the research competences of a future teacher is the dominance of the information-reproductive (knowledge) model of organizing the educational process. It does not actualize research functions enough.Based on generalizing various positions of scientists, an author’s approach to interpreting the investigated phenomenon is proposed, centered on its functionality. The results of the diagnostics of the level of formation of the research competence of junior and senior students are presented. They showed a slight increase in quality indicators according to this criterion. This indicates the problem of orientation of traditional education on the development of this group of competencies. Also this indicates the need for more active use of the capabilities of the competency-based education system. It is substantiated the objective need for reorientation of teaching/studying of academic disciplines (including special ones) of the above-mentioned special and other academic disciplines in the context of transition to a competency-based system of professional education. Based on the analysis of the diagnostic results, a set of reasons has been formed. They are classified as the most significant in the context of ensuring the effectiveness of the development of students’ research competencies. The need to work purposefully on improving traditional practices of organizing educational activities, gradually increasing the research component, is integrally determined. At the same time, there is a need for rethinking the concept and methodology of studying various academic disciplines, especially special ones.